A joint decoding algorithm for turbo product codes applied in PCM/FM telemetry system - Li Wang; Manxi Wang; Liandong Wang; Fu Yuan (2014 7th International Congress on Image and Signal Processing, 2014)
For decreasing the high computational complexity of Turbo product code in PCM/FM telemetry system, a joint decoding algorithm based on syndrome-based decoding and a correlation operation to substitute for searching the competing codeword was proposed. Simulation results show that the proposed algorithm can effectively reduce the decoding complexity with less coding gain degradation.